Local tissue reaction on grafts at its implanting into anterior abdominal wall tissues and ways of its improvement. - Pikaluk, V. S.; Hryvenko, S. H.; Shalanin, V. V.; Hatipov, A. S.; Zhuravel, E. A.; Asanova, Z. V. (Морфологія / Morphologia / Morfologìâ, 2014)
Background. In Ukraine surgical intervention because of hernia re-present 8-10% among other operations. Significant deficiency of any graft material is a manifestation of the local inflammatory process that occurs in response to the implantation of foreign material into the body. In this regard the development of synthetic materials which will cause a minor inflammatory response while maintaining a satisfactory strength characteristics and manufacturing cost. Objective. To experimentally approve the possibilities of processing the grafts with autogenous blood plasma and cattle cerebrospinal fluid for the reduction of tissue inflammatory reaction. Methods. 36 adult male rats were operated under ether narcosis with implantation of a polypropylene mesh endoprosthesis Alfa Vita 90 into anterior abdominal wall. Animals were divided into 2 groups: control, where grafts were processed with autogenic blood plasma, and experimental, with grafts processed with cattle cerebrospinal fluid. After 7, 14, 21 and 28 days after operation fragments of anterior abdominal wall were taken for histological analysis. Results. Intensity of local aseptic inflammatory reaction around the elements of the polypropylene mesh prosthesis in all terms was more intensive in the control group with continuous amplification till the 28th day after surgical intervention. While in experimental animals on the 28th day after graft implantation inflammatory signs were not visualized. Conclusion. Processing of polypropylene mesh implants with autologous blood plasma and cattle cerebrospinal fluid reduces the local inflammatory reaction after implantation in the anterior abdominal wall, decreasing the risk of local complications in the postoperative period.